Corporate social responsibility and Islamic banks: a systematic literature review - Zafar, Muhammad Bilal; Sulaiman, Ahmad Azam (Springer Verlag, 2019)
Although CSR is an extensively studied topic, a systematic, comprehensive and diverse review in the domain of CSR and Islamic banking is missing. This paper intends to present a broad review of this domain. Through a state-of-the-art review, we have divided the paper into different sections, the first two are general i.e. CSR measurement, it deals with measuring methods of CSR in Islamic banking, and CSR theories, it gives a brief overview of theories referred in under-review studies. While, the other three sections are separated according to the nature of studies i.e. CSR narrative under the Islamic paradigm, CSR disclosure by Islamic banks, and CSR exposition in Islamic banks. At the end of each section, we have included a ‘commentary’ to discuss and summarize major points, highlight trends and issues, provide insights into limitations and suggest future research directions.